1994
DOI: 10.1080/00140139408963624
|View full text |Cite
|
Sign up to set email alerts
|

The influence of triazolam and flunitrazepam on isokinetic and isometric muscle performance

Abstract: The influences of two benzodiazepines (triazolam 0.25 mg and flunitrazepam 2 mg) on isokinetic and isometric muscle performance and on cardiovascular parameters were examined after a standard period of sleep. A randomized and double-blind test procedure was used (n = 15). Triazolam had no significant (p < 0.05) influence on either of the test conditions. Administration of flunitrazepam significantly lowered values for maximal isometric force and for the cardiovascular parameters. It was concluded that triazola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Both muscle weakness and poor balance are risk factors for falls [ 11 , 27 ], and benzodiazepines are known to impair muscle strength and balance [ 16 , 28 ]. Even though the fundamental aim of the present study was to provide tools for fall and fracture prevention in a clinical context, this study was not designed to register participants’ falls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both muscle weakness and poor balance are risk factors for falls [ 11 , 27 ], and benzodiazepines are known to impair muscle strength and balance [ 16 , 28 ]. Even though the fundamental aim of the present study was to provide tools for fall and fracture prevention in a clinical context, this study was not designed to register participants’ falls.…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism for the possible reduction of risk of falls and fractures after benzodiazepine withdrawal could be enhanced balance and muscle strength. Although the use of psychoactive medications has been connected to lowered muscle strength [ 15 ], clinical studies specifically concerning benzodiazepines and muscle strength are rare [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although clinically all benzodiazepines cause a dose-related central nervous system depressant activity varying from mild impairment of task performance to hypnosis, it has been demonstrated that nightly administration of 10 mg of temazepam has little influence on the recovery of subjective, physiological and performance measures in either elite athletes or sedentary subjects after a west-bound flight across five time zones (Reilly et al 2001). Although it has been also shown that triazolam does not influence sport performance, flunitrazepam significantly lowered values for maximal isometric force and the cardiovascular parameters, thereby negatively affecting a variety of strength characteristics and several cardiovascular parameters during physical exercise (Zinzen et al 1994). Clearly, the manipulation of foods and/or beverages with ''performance-decreasing substances'' having the potential to produce sedative, hypnotic, muscle relaxant and amnesic actions cannot be considered a typical form of ergogenic aid, but nonetheless raises the possibility that this and other forms of ''doping to lose'' might be administered by athletes to either team-mates (in order to lose games) or opponents (in order to win games).…”
mentioning
confidence: 96%